Salmonella Typhimurium reprograms macrophage metabolism via T3SS effector SopE2 to promote intracellular replication and virulence - Jiang, Lingyan; Wang, Peisheng; Song, Xiaorui; Zhang, Huan; Ma, Shuangshuang; Wang, Jingting; Li, Wanwu; Lv, Runxia; Liu, Xiaoqian; Ma, Shuai; Yan, Jiaqi; Zhou, Haiyan; et al. (Nature communications, 2021)
Salmonella Typhimurium establishes systemic infection by replicating in host macrophages. Here we show that macrophages infected with S . Typhimurium exhibit upregulated glycolysis and decreased serine synthesis, leading to accumulation of glycolytic intermediates. The effects on serine synthesis are mediated by bacterial protein SopE2, a type III secretion system (T3SS) effector encoded in pathogenicity island SPI-1. The changes in host metabolism promote intracellular replication of S . Typhimurium via two mechanisms: decreased glucose levels lead to upregulated bacterial uptake of 2- and 3-phosphoglycerate and phosphoenolpyruvate (carbon sources), while increased pyruvate and lactate levels induce upregulation of another pathogenicity island, SPI-2, known to encode virulence factors. Pharmacological or genetic inhibition of host glycolysis, activation of host serine synthesis, or deletion of either the bacterial transport or signal sensor systems for those host glycolytic intermediates impairs S . Typhimurium replication or virulence. Salmonella Typhimurium establishes systemic infection by replicating in host macrophages. Here, Jiang et al. show that infected macrophages exhibit upregulated glycolysis and decreased serine synthesis, leading to accumulation of glycolytic intermediates that promote intracellular replication and virulence of S . Typhimurium.